A systems approach to creative flourishing: conceptual foundations and implications for development - Glass, Cordele (Frontiers in Psychology, 2025)
This article introduces the term “Creative Flourishing” defined as the experiential confluence of Creative Agency (one's drive to create), Creative Self-Efficacy (belief in one's creative ability), and Flow Proneness (the tendency to experience flow during creative activities) within an appropriate and responsive environment. When an individual experiences each of these aspects together they can assert that they are driven to create, they feel they have the ability to be creative, and they enjoy creating. Thus, Creative Flourishing is the result of the harmonious alignment of one's creative desires, self-perception of skills, and experiences within their context. This paper synthesizes existing literature to define Creative Flourishing, reviews intervention strategies aimed at cultivating awareness of its components, and discusses potential measures for assessing growth in these areas.